Maternal LINE-1 DNA Methylation and Congenital Heart Defects in Down Syndrome - Babić Božović, Ivana; Stanković, Aleksandra; Živković, Maja; Vraneković, Jadranka; Mahulja-Stamenković, Vesna; Brajenović-Milić, Bojana (Frontiers in Genetics, 2019)
Down syndrome (DS) is one of the most common chromosomal abnormalities associated with congenital heart defects (CHD), with approximately 40% to 60% of cases showing cardiac defects. This study assessed (i) the association between maternal LINE-1 methylation and the occurrence of CHDs in children with DS and (ii) the impact of endogenous maternal factors (MTHFR C677T polymorphism and maternal age) and exogenous maternal factors (cigarette smoking, alcohol intake, medication use, body mass index, and dietary habits such as folate intake) on maternal LINE-1 methylation and on the occurrence of CHD in DS. Patients and methods: The study included 90 mothers of children with DS of maternal origin (49% DS-CHD+ mothers/51% DS-CHD- mothers). LINE1 DNA methylation was analyzed in peripheral blood lymphocytes by quantification of LINE-1 methylation using the MethyLight method. MTHFR C677T polymorphism genotyping was performed using PCR-RFLP. Results: LINE-1 methylation was not significantly different between DS-CHD+ and DS-CHD- mothers (P=0.997). Combination of MTHFR C677T genotype/diet and BMI were significant independent predictors of LINE1 DNA methylation in DS-CHD+ mothers (β -0.40, P=0.01 and β -0.32, P=0.03, respectively). In the analyzed multivariate model (model P<0.028), these two factors explained around 72% of the variance in LINE1 DNA methylation in mothers of children with DS and CHD. The group with the highest BMI (≥30 kg/m2) had significantly lower LINE-1 methylation than the group with normal BMI (Bonferroni post-hoc P=0.03) and the overweight group (Bonferroni post-hoc P=0.04). The lowest LINE1 DNA methylation values were found in DS-CHD+ mothers with the CT+TT genotype and a low-folate diet; the values were significantly lower than the values in mothers with the CC genotype and a folate-rich diet (Bonferroni post-hoc P=0.04). Conclusion: Association between maternal LINE1 methylation and CHD in children with DS was not found. Study showed that the MTHFR genotype/diet combination and BMI were significantly associated with LINE-1 methylation in mothers of children with DS-CHD+. These results highlight the need for a multifactorial approach to assess the roles of endogenous and exogenous maternal factors in maternal LINE1 methylation and the consequent pathologies in children. Extensive studies in a larger sample may help elucidate these relationships.